2018
DOI: 10.31234/osf.io/mkatf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of A Group Counseling Intervention On Students With Behavioral Adjustment Problems

Abstract: Cognitive-behavioral group counseling was studied with students that exhibited externalizing behavior. A total of 24 male students (12 control and 12 experimental) who exhibited externalizing behavior participated in this study. The intervention resulted in clear and salutary changes in the behavioral adjustment of students. The intervention demonstrates that school counselors can play a substantial role in remediating and preventing disruptive behavior in schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Students’ grade level ranged from kindergarten to eighth grade, with students in third grade studied most often. Across studies, 51.58% of participants were male, with four studies including only males (Guevremont & Foster, 1993; Nelson et al, 1996; Quinn, 2002; Robinson et al, 2002) and one study including only females (Leff et al, 2009). Of those studies reporting participants’ race, the overall sample included the following: 33.36% Caucasian, 28.02% African American, 25.14% Hispanic, and 12.66% other or not reported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Students’ grade level ranged from kindergarten to eighth grade, with students in third grade studied most often. Across studies, 51.58% of participants were male, with four studies including only males (Guevremont & Foster, 1993; Nelson et al, 1996; Quinn, 2002; Robinson et al, 2002) and one study including only females (Leff et al, 2009). Of those studies reporting participants’ race, the overall sample included the following: 33.36% Caucasian, 28.02% African American, 25.14% Hispanic, and 12.66% other or not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Of those studies reporting participants’ race, the overall sample included the following: 33.36% Caucasian, 28.02% African American, 25.14% Hispanic, and 12.66% other or not reported. The remaining participants ( n = 41, 0.82% of participants) were included in studies that reported race for the overall school population (Elias & Hoover, 1997; Nelson et al, 1996) or did not report students’ racial background (Guevremont & Foster, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations